Aplicação de estruturas zeolíticas de imidazólio (ZIFs) no desenvolvimento de membranas de matriz mista para separação de gases - Eiras, Daniel (Universidade Federal de São Carlos, 2012)
Mixed matrix membranes based on a glassy polymer and a zeolite with organic character were developed, in order to evaluate whether the organic character of the ZIF-8 would favor its incorporation in the polymer matrix as a result of better compatibility between the phases and also the efficiency of this zeolite of improving the ideal selectivity of the polymer for two gas pairs, CO2/CH4 and CO2/N2. ZIF-8 particles were incorporated to the polymer matrix by solution mixing with an ultrasound. The membranes were prepared by solution casting, followed by solvent evaporation under a controlled atmosphere in a glove bag. Results showed a significantly improvement in CO2/N2 ideal selectivity with the incorporation of ZIF-8 when compared to the ideal selectivity of the membrane. A 17% increase in the ieal CO2/N2 selectivity was obtained with the incorporation of 30%wt of ZIF-8. The result was accompanied by a significantly increase in the membrane permeability. It is also presented the influence of residual solvent in the properties of the membranes. Finally strong experimental evidences of ZIF-8 compressibility were obtained. It can be concluded based on the results that the organic character of ZIF-8 favors its incorporation in the polymer matrix when compared to the inorganic zeolites and that zeolitic imidazolate framework can be considered a promising technology for the development of mixed matrix membranes for gas separation.
Application of zeolitic imidazolate frameworks for the development of mixed matrix membranes for gas separation
Keywords: Polímeros; Membranas de separação; Peneiras moleculares; Permeação de gases; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA